The popular on record: universities, museums, and images in heritage games in the Brazilian Northeast (Tempo e Argumento, 2024)
Amid heritage games, the aim of this piece is to highlight some registration movements and studies on popular art and culture of the Brazilian Northeast during the 1960s, stressing the role of universities. After taking as object of analysis the construction of the meanings of popular in the Movimento Folclórico Brasileiro (MFB), we investigated the mobilization of the concept of popular culture present in the experiences of the Museu de Arte da Universidade Federal do Ceará (MAUC), in the creation of the Museu de Arte Popular da Universidade Federal da Bahia (MAP) and in the Instituto de Estudos Brasileiros (IEB) da Universidade de São Paulo (USP). In the study, we situate the heritage games by examining the images of the popular they create, respectively, through the formation of the Coleção de Arte Popular, the assembly of exhibitions with the Brazilian Northeast as subject, and the audiovisual recording through documentary cinema.
Keywords: popular; university; heritage; Brazilian Northeast